Effect of high energy electron irradiation on the electromechanical properties of poly (vinylidene fluoride-trifluorethylene) 50/50 and 65/35 copolymers - Cheng, Z Y (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2000)
High energy electron irradiation with a broad range dosage was carried out on poly(vinylidene fluoride trifluorethylene) copolymer 65/35 mol% and 50/50 mol% films at different temperatures from room temperature to a temperature close to the melt temperature. The effect of irradiation on the properties of the films, such as electric field-induced strain, dielectric and polarisation behaviors, and mechanical modulus, is presented. The irradiated films can exhibit a very large electric field-induced strain, more than 4.5% longitudinal strain, and 3% transverse strain. The transverse strain of the stretched film can compare with the longitudinal strain; that of the unstretched film is much smaller than the longitudinal strain. With regard to the dielectric and polarization behaviors, we found that irradiation changes the copolymer from a typical ferroelectric to a relaxor ferroelectric in which the behavior of microregions under the electric field plays the key role. Between the two copolymers studied, we found that the 65/35 copolymer is preferred for both longitudinal and transverse strain generation. A model is proposed to explain the experimental results that the amplitude of the charge electrostrictive coefficient (Q) increases with decreasing crystallinity